The study of informational professional field of pharmacy specialists - N. O. Tkachenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Today professionalism is important not only for the characteristics of an individual, but also for the manifestation of professional activities. Self-education, self-training and training on the working place are integral elements of the whole continuous professional development. Various components of professionalism form the social responsibility of pharmacist in contemporary conditions. During all professional activities of pharmacists the continuous formation of administrative, economic, legal, communication, social and information competence takes place. Professionally oriented periodical publications, scientific and practical activities act as assistants in it.